Beverage coaster case - Ariff, Ahmad Fairuz; Raja Ahmad Effendi, Raja Ahmad Azmeer; Baharuddin, Nasir (Universiti Putra Malaysia Press, 2013)
A coaster is a base to rest a glass or cup upon. The main purpose is to protect the table surface from dirt or water spilling. As it is not being properly kept, coasters are usually misplaced after being used and this will cause inconvenience to users. In order to keep this product intact, it is important to design a container that will serve this purpose. As a result, a coaster container is designed. It is based on the stylization process of shapes with reference to the Rhinocerous beetle. Besides incorporating an impressive appearance in its design and styling, the five peace coaster that is included in a set is printed with a series of different types of Rhinocerous beetles as added information to users. Moreover, the coaster set may be used as a decorative item for the users, as well as an advertising and promotional item which serve as perfect executive business gifts.